Influence of sales representative characteristics on customer purchase behaviour. (15th January 2021) - Gautam, Shalini; Agarwal, Sakshi; Kumar, Utkarsh
The present study examines the influence and effectiveness of sales representative in an emerging market in enhancing retail sale in cases of a high involvement product like apparel and low involvement product like grocery. The present research examined the effect of five factors, namely, sales representative's personal characteristics, competence, sales representative's-initiated promotion, involvement and ethical behaviour on purchase behaviour of consumers. The step-wise regression method was used to support the proposed hypotheses. The results of the study concluded that in both high and low involvement product category, sales representative's-initiated promotion and involvement affect the purchase behaviour of consumers. Other than these two factors, the competence of the salesperson plays an important role in high involvement products, whereas his personal characteristics are important in case of low involvement products. The research provides a guide for sales managers for developing a training and strategy development program for their sales force.